Dampak Penghapusan E-Commerce Tiktok Shop terhadap Tingkat Pendapatan Pelaku UMKM di Pasar Sentral Kabupaten Pangkajene dan Kepulauan - Kapriani, Kapriani; Hardianti, Hardianti; Jumarti, Jumarti (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
This research aims to determine the impact of eliminating the Tiktok Shop e-commerce on the income level of MSMEs. This research uses primary data and also secondary data. The research method used was saturated sampling with a total of 45 respondents. The data analysis technique used is validity test, reliability test. Testing the analysis model in this research uses simple linear regression analysis, T test and R determination. Based on the research results, it shows that the independent variable e-commerce TikTok shop has a significant effect on the dependent variable MSME Income Level (Y). Based on the research results, it shows that the value of tcount > ttable or 1.997 > 1.679 and a significant value of 0.045 < 0.05, then Ha is accepted and Ho is rejected, so that partially the price has a significant effect on MSME income in the Main Market of Pangkajene and Islands Regency